2002
DOI: 10.1142/s0218339002000767
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Evolving Proteomes: Predictions of the Number of Protein Domains in Nature and the Number of Genes in Eukaryotic Organisms

Abstract: Motivation: Obtaining accurate estimates of the numbers of protein-coding genes and protein domains in a proteome, and the number of protein domains in nature is a daunting challenge. Computational analysis of the protein domain sets in the proteomes of many species allows us to estimate these numbers and to find their evolution relationships.Results: We have analyzed the distributions of the number of occurrences of protein domains in sample proteomes of the 70 fully sequenced genome organisms of three major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This distribution suggests an appearance of hub nodes in the corresponding functional networks of proteins. Due to the non-zero value parameter b , the network is a scale dependent network [ 8 , 18 ]. This indicates an additional mechanistic source of functional complexity of interconnections of splice variants and protein functions in human.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution suggests an appearance of hub nodes in the corresponding functional networks of proteins. Due to the non-zero value parameter b , the network is a scale dependent network [ 8 , 18 ]. This indicates an additional mechanistic source of functional complexity of interconnections of splice variants and protein functions in human.…”
Section: Resultsmentioning
confidence: 99%
“…Note, similar statistics could emerge in the random graphs when a nodal degree distribution in the graph follows asymptotically (at large enough m ) GDP function with constant exponent ( k+1 ), where k+1 ≈3 and b =0 [ 17 ]. The distribution function of the events could be described as a stochastic process, which has no or very minor influence on restrictions and/or evolution-driven connections [ 7 - 9 , 18 , 25 - 27 ]. Thus, by a scale-free network model, a new biological function could be acquired or lost by a TU almost arbitrarily with or without selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…They found that a majority of domain families are common to all three kingdoms of life and thus likely to be ancient. Kuznetsov et al [43] performed a similar analysis using InterPro domains and found that only about one fourth of all such domains were present in all three kingdoms, but a majority was present in more than one of them. Lateral gene transfer or annotation errors can cause a domain family to be found in one or a few species in a kingdom without actually belonging to that kingdom.…”
Section: Kingdom and Age Distribution Of Domain Families And Architecmentioning
confidence: 99%
“…Later work ( [39,43], see also [44]) demonstrated that proteome-wide domain occurrence data fit the general GPD better than the power law but that it also asymptotically fits a power law as X ) i. The deviation from strict power law behavior depends on proteome size in a kingdom-dependent manner [43]. Regardless, it is mostly appropriate to treat the domain family size distribution as approximately (and asymptotically) power law-like, and later studies typically assume this.…”
Section: Distribution Of the Sizes Of Domain Familiesmentioning
confidence: 99%
See 1 more Smart Citation